A mobile genetic element in Serratia marcescens, a causative agent of onion disease - Ovcharenko, L.P.; Voznyuk, T.M.; Zaetz, I.E.; Potopalsky, A.I.; Reva, O.N.; Kozyrovska, N.O. (Вiopolymers and Cell, 2010)
Aim. To screen mobile genetic elements (MGE) in the bacterium which caused decay of field-grown onion bulb and to study an integron and gene cassettes associated. Methods. Polymerase chain reaction (PCR) and PCR products sequencing were used for both the bacterium and MGE identification. Terminally-labeled Restriction Fragment Length Polymorphism (TRFLP) analysis was performed for detection of any bacterium in the onion bulb tissue. Results. The bacterium, which caused field-grown onion decay, was identified by nucleotide sequence analysis of the 16S rRNA genes to be S. marcescens known as phytopathogen. However, this isolate did not respond to specific primers designed for pathogenic strains. Inoculation of onion (Allium cepa L.), Arabidopsis thaliana (L.) Heyhn, and lettuce (Lactuca sativa) seeds resulted in biomass promotion of symptomless plants. PCR revealed the presence of a class 1 integron in S. marcescens IMBG291 which represents the first isolation of this integron in phytopathogenic Serratia species. The gene cassettes harbored by the integron have been represented with the promoterless genes encoded formimino-glutamate deiminase and ascorbate-specific phosphotransferase system enzyme IIC, and with additional three senseless sequences flanked by a 59-bp element. Conclusion. S. marcescens IMBG291 exhibited plant growth promotion or pathogenicity, depending on the environmental situation, due to horizontally acquired new gene cassettes located in the integron.